INVESTIGATION OF THE INTERACTION BETWEEN THE MOVING SEPARATOR SCREEN SURFACE AND THE COTTON MASS - Pirnazarov, Ulugbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article theoretically substantiates an improved design of a cotton separator device that separates cotton from the air stream. In the proposed modification, the mesh surface in the working chamber of the device has been structurally altered compared to existing analogues — its volume was optimized, and it was mounted as a moving surface. A mathematical model of the process was developed, and corresponding graphical results were obtained to analyze the dynamics of cotton-air separation.